"CULTURED CLINICIANS": THE RHETORIC OF CULTURE IN CLINICAL PSYCHOLOGY TRAINING - Eagle, Gillian (PINS-Psychology in Society, 2026)
The article examines the vexing question of the status of "culture" in contemporary clinical psychological training in South Africa. The interest in this topic arises out of some puzzlement and frustration in attempting to engage with "cultural" critiques of clinical practice and the slippery, contested and idealized elements of the construct. The article is particularly interested in the rhetorical power of the term and the discursive functions it performs as spoken by different speakers in different contexts. Rather than rehearsing the many anthropologically based debates about the scope and definition of the term culture, the focus is on how the term is employed in arguments about the nature of clinical practice/sin South Africa. Several authors (for example, Dawes, 1998; Hayes, 1998; Gibson, Sandenbergh & Swartz, 2001; Moll, 2002) have engaged in related discussions pertaining to ethnicity, "africanisation" and appropriate theory and training models as they relate to psychology in post-colonial and post-apartheid South Africa. Such writing reflects the widespread contestation concerning the adoption of so called Western and Eurocentric theories and practice and the basis on which these should be ousted or retained. Whilst the content of such arguments will be addressed to some extent, the focus of the article is on the multiple meanings served by the term culture and on some of the politics entailed in speaking about culture in clinical training settings. The discussion is based both on naturalistic observation in a university environment as well as upon formal interviews with a range of psychologists of different levels of experience, from different training backgrounds and from varied "race" and class origins, all engaged in clinical psychology training. The article examines how culture is framed and employed at a point in South African history when transformation is part of the national educational and political agenda. Although the issues raised relate to a particular training context, it is hoped that the discussion will stimulate wider debate about the "rules of engagement" in relation to sensitive topics in contexts of old and new power relations.